KNOW MY BODY, TAKE CARE OF MY BODY - Anggraeni, Lina Dewi; Daryati, Elisabeth Isti; Febiola, Yelli; Melanurista, Adelheid; Oktavia Roma Uli, Yohana; Gabriela, Maria; Rina Martines, Krisna (LPPM Univ. Ibn Khaldun Bogor, 2023)
Adolescence is a time of rapid growth and development both physically, psychologically and intellectually. Adolescents are characterized by a pronounced curiosity. High levels of curiosity in adolescents often lead to problems, including reproductive health issues. This community service activity aims to increase students' knowledge in terms of development, changes that occur in adolescents, and how to perform proper personal hygiene. The method used in this activity is to provide counseling on knowledge about adolescents and their problems and reproductive health. This activity was conducted offline and was aimed at 4th, 5th and 6th grade students at SD Negeri Tugu Utara 19 North Jakarta. This charitable activity ran smoothly and was well received by the school and students. After counseling, there was an increase in knowledge about reproductive health from the participants to 94.8%.